Roles of green intellectual capital facets on environmental sustainability in Oman. Issue 3 (25th December 2023) - Gharib, Moaz; Alam, Md Shabbir; Hawaldar, Iqbal Thonse; Murshed, Muntasir; Khan, Uzma; Alvarado, Rafael; Rehman, Ijaz Ur
Abstract: The present study determines the impacts of different types of green intellectual capital such as green human capital, green structural capital, and green relational capital on environmental sustainability in the Sultanate of Oman. It has become a crucial aspect to analyze the effect of green intellectual capital on ecological sustainability. A simple random sample technique is used to assemble data using a structured questionnaire from 205 respondents working at Raysut Cement Company and Salalah Methanol Company in Oman. The covariance-based equation in the structural modeling perspective is used to examine data. The study's results reveal that green structure-based capital is the only dimension of green Intellectual capital that significantly affects environmental sustainability. In contrast, green human capital and relation-based capital do not substantially affect ecological sustainability. Conclusively, this study also provides ecological strategies that can be useful to enrich organizations to accomplish sustainability.